Association of CYP3A5 polymorphisms and parathyroid hormone with blood level of tacrolimus in patients with end‐stage renal disease. Issue 5 (31st May 2021) - Tanaka, Ryota; Suzuki, Yosuke; Watanabe, Hiroshi; Fujioka, Takashi; Hirata, Kenshiro; Shin, Toshitaka; Ando, Tadasuke; Ono, Hiroyuki; Tatsuta, Ryosuke; Mimata, Hiromitsu; Maruyama, Toru; Itoh, Hiroki
Abstract: Because tacrolimus is predominantly metabolized by CYP3A, the blood concentration/dose (C/D) ratio is affected by CYP3A5 polymorphism. Parathyroid hormone (PTH) expression increases in secondary hyperparathyroidism, which is frequently associated with end‐stage renal disease. Recently, PTH has been shown to downregulate CYP3A expression at mRNA level. In this study, we examined the influence of CYP3A5 polymorphism on and association of serum intact‐PTH (iPTH) level with blood tacrolimus concentration in patients with end‐stage renal disease just before kidney transplantation. Forty‐eight patients who satisfied the selection criteria were analyzed. Subjects were classified into two phenotype subgroups: CYP3A5 expressor (CYP3A5*1/*1 and *1/*3; n  = 15) and CYP3A5 nonexpressor (CYP3A5*3/*3; n  = 33). The blood tacrolimus C/D (per body weight) ratio was significantly lower in CYP3A5 expressors than that in CYP3A5 nonexpressors. A significant positive correlation was found between tacrolimus C/D and iPTH concentrations ( r  = 0.305, p  = 0.035), and the correlation coefficient was higher after excluding 20 patients co‐administered CYP3A inhibitor or inducer ( r  = 0.428, p  = 0.023). A multiple logistic regression analysis by stepwise selection identified CYP3A5 polymorphism and serum iPTH level as significant factors associated with tacrolimus C/D. These results may suggest the importance of dose design considering not only the CYP3A5 phenotype but also serum iPTH level when using tacrolimus in patients who undergo renal transplantation.